Diagnosis of skin and soft tissue infections using near‐infrared spectroscopy. Issue 1 (3rd May 2021) - Oi, Marina; Maruhashi, Takaaki; Kumazawa, Kenichi; Iwakawa, Saori; Kurihara, Yutaro; Wato, Jyunpei; Niimi, Yuta; Takeda, Akira; Asari, Yasushi
Abstract : Aim: Skin and soft tissue infections are classified into cellulitis and necrotizing fasciitis, which are difficult to distinguish. Necrotizing fasciitis has a poor prognosis and requires immediate intensive care. The diagnostic gold standard is to incise the lesion to determine whether necrosis has reached the fascia. We aimed to show that these infections can be differentiated using near‐infrared spectroscopy. Methods: We describe two cases in an observational study about the utility of near‐infrared spectroscopy. Case 1 involved a 77‐year‐old man with a chief complaint of pain, redness, and swelling in the right lower leg for 1 week. Computed tomography of his legs showed no gas formation. Case 2 involved an 82‐year‐old man. He visited another hospital because of pain, redness, and swelling in the right thigh. Based on the X‐ray examination, necrotizing fasciitis was suspected, and he was transferred to our hospital. Results: In Case 1, the regional oxygen saturation value was lower on the lesion side (41%) than on the healthy side (55%). We confirmed the depth of invasion by incision, leading to a diagnosis of necrotizing fasciitis. In Case 2, the thigh's regional oxygen saturation was higher on the affected side (76%) than on the healthy side (61%). An incision was made for diagnosis, but the fascia was not necrotized. Thus, we diagnosed cellulitis and provided conservative treatment using antibiotics. Conclusion: Near‐infrared spectroscopy can be utilized to measure tissue blood flow, and it could be useful as a non‐invasive diagnostic tool for skin and soft tissue infections. Abstract : Currently, the diagnosis of necrotizing fasciitis is made by surgical incision. In this paper we report on a new diagnostic tool for Skin and soft tissue infections.